Book Review: M. Darmell and K. Rampal, Connected or Disconnected: The Art of Operating in a Connected World. Issue 4 (December 2018) - Acharya, Ira
M. Darmell and K. Rampal, Connected or Disconnected: The Art of Operating in a Connected World, 2017, New Delhi: SAGE Publications, 158 pp., ₹395. ISBN: 978-93-866-0277-0.